FTIR-based measurements of self-broadening and self-shift coefficients as well as line strength in the first overtone band of HCl at 1.76µM - Li, Gang; Serdyukov, Anton; Gisi, Michael; Werhahn, Olav; Ebert, Volker (Journal of quantitative spectroscopy & radiative transfer, 2015)
FTIR spectra of the 2-0 band of HCl have been measured in the 5300-5900cm−1 spectral region at 15 different pressures (0.05-2.5bar) and at a spectral resolution of 0.07cm−1. For the first time, reliable and consistent self-induced broadening and shift coefficients for the complete HCl 2-0 band have been reported. Line intensities determined from a robust regression analysis with improved uncertainties are also presented.
Gesehen am 18.06.2020